A new species of Pontonema (Oncholaimidae, Nematoda) and a redescription of Pontonema incisum Wieser, 1953 from Santa Cruz and Chubut Provinces, Argentina - Villares, Maria Gabriela (2015)
Pontonema golfonuevensis sp. nov. from Chubut Province, Argentina is described and a description of the male of Pontonema incisum Wieser, 1953 from Chubut and Santa Cruz provinces is provided. Pontonema golfonuevensis sp. nov. is characterized by having the slender sub-ventral teeth 25 µm long located at 24 % of stoma length, a short, broad dorsal tooth at 60 % of stoma length, excretory pore opening at level of base of the buccal cavity, and by having a ventral precloacal sensory field with four papillae and a glandular sub-ventral area with seven papilliform sensillae. The male of P. incisum has long slender sub-ventral teeth at 36 % of stoma length, a short broad dorsal tooth at 72 % of stoma length, excretory pore about two buccal cavity lengths from the anterior end, and a ventral precloacal sensory field without papillae and a glandular sub-ventral area with twelve to fourteen papilliform sensillae. A key for identification of males of Pontonema is presented.